Empirical Analysis of the SAC-OCDMA-WDM System by Leveraging the AND Subtraction Technique - Islam, Fahmidul; Uddin, Mohammad Nasir (AIUB Journal of Science and Engineering (AJSE), 2024)
This study utilized C-band carrier frequency to evaluate Spectral Amplitude Coding Optical Code Division Multiple Access (SAC-OCDMA) systems, employing Fiber Bragg Gratings (FBG) as encoders and decoders and implementing the AND subtraction detection technique. The system's performance is influenced by various factors, including optical transmission distance, optical power, channel bandwidth, data rate, and the number of channels. Extensive simulations were conducted to examine the impact of these parameters on system performance. The proposed SAC-OCDMA system was integrated with a Wavelength Division Multiplexing (WDM) system to increase the number of active channels. The network was designed and analyzed using commercially available Optisystem software. The proposed SAC-OCDMA system architecture with two channels maintained operational limits up to unrepeated transmission over 336 km at a data rate of 1.6 Gbit/s, achieving results within the pre-FEC threshold. Additionally, the SAC-OCDMA system was simulated with up to ten channels, considering the pre-FEC bit error rate threshold. The results were compared with recent technical articles and were found to be superior in terms of the number of channels and transmission distance. The proposed model achieved a superior data rate of 6.4 Gbps and a maximum transmission distance of 24 km for a 10-channel architecture.